Activity‐Fed Translation (AFT) Assay: A New High‐Throughput Screening Strategy for Enzymes in Droplets. Issue 9 (7th May 2015) - Woronoff, Gabrielle; Ryckelynck, Michaël; Wessel, Julia; Schicke, Olivier; Griffiths, Andrew D.; Soumillion, Patrice
Abstract There is an increasing demand for the development of sensitive enzymatic assays compatible with droplet‐based microfluidics. Here we describe an original strategy, activity‐fed translation (AFT), based on the coupling of enzymatic activity to in vitro translation of a fluorescent protein. We show that methionine release upon the hydrolysis of phenylacetylmethionine by penicillin acylase enabled in vitro expression of green fluorescent protein. An autocatalytic setup where both proteins are expressed makes the assay highly sensitive, as fluorescence was detected in droplets containing single PAC genes. Adding a PCR step in the droplets prior to the assay increased the sensitivity further. The strategy is potentially applicable for any activity that can be coupled to the production of an amino acid, and as the microdroplet volume is small the use of costly reagents such as in vitro expression mixtures is not limiting for high‐throughput screening projects.